A Viable Insolvency Procedure for Sovereigns in the Euro Area. (27th July 2015) - Fuest, Clemens; Heinemann, Friedrich; Schröder, Christoph
Abstract: A mechanism to restructure the debt of an insolvent euro country is a missing element in the emerging institutional architecture of the euro area. The introduction of an insolvency procedure for sovereigns faces a dilemma: in the foreseeable future, its introduction would risk pushing Europe back into acute crisis; but the indefinite postponement of reform would impair the credibility of a future regime change. Against this background, this article reviews arguments and existing blueprints for sovereign insolvency procedures in the euro area and develops a Viable Insolvency Procedure for Sovereigns. This procedure avoids any sudden measures which could destabilize the present fragile situation but carefully designs an irreversible transition toward the new regime. The proposal comprises two pillars: an insolvency procedure for the long run and a credible bridge toward that system.